Computational Fluid Dynamic for Performance Hydrofoil due to Angle of Attack - Maria Margareta Zau Beu (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2020)
This study uses a 2-D computational fluid dynamic (CFD) with a hydrofoil object. The general parameters used are pressure-based with Reynold numbers (Re) 106. The Pressure velocity coupling method used is SIMPLE with Reynold k-? as the viscous model on ANSYS Fluent 2019R1. The angle of attack variations are used starting from 00, 20, 40, 60, 10, 120, 150, 200, 250, and 300. From the simulation shows the hydrofoil characters depicted in the Coefficient drag (CD), Coefficient Lift (CL) and Pressure graphs Coefficient (CP) approaches the experimental results.